St. Andrew's project: building inclusion using 'outcomes that matter' - Chris Walter (Scottish Journal of Residential Child Care)
The article will describe how Camphill, an independent residential school for children and young people with a variety of complex needs, began a new project (St. Andrew’') by applying its experience in using relationship-based approaches to work positively with vulnerable individuals. The children and young people we work with do not fit in any standard programme being either too able for a special school or too complex for mainstream schooling. The origins of the St. Andrew's Project lie in the original vision of Camphill as a place of mutual learning, where each individual's spiritual uniqueness is promoted through meaningful relationships. This core belief resonates with the Circle of Courage model of meeting four fundamental growth needs for belonging, mastery, independence and generosity (Brendtro, Brokenleg and van Bockern, 1990). Therapeutic support is negotiated with children, their families and supporting agencies following a comprehensive ecological assessment. The intended outcomes for any short or medium term intervention are then agreed with those involved using the Outcomes that Matter © framework (Fulcher and Garfat, 2012). Weekly discussions with each young person then form the basis of an outcome based intervention plan.